Using English Songs to Teach Vocabulary in an Elementary School - Sri Rejeki Murtiningsih; Anisa Wahyu Dwi Putri; Indah Puspawati (Universitas Muhammadiyah Yogyakarta, 2023)
Despite the limited number of students, several teaching and learning activities have been conducted online and face-to-face during the pandemic. Accordingly, it becomes a challenge for elementary school teachers in their English teaching practice as students are more focused on mastering vocabulary. Therefore, teachers should create a pleasant and joyful classroom to ensure students learn English effectively. According to that background, English teaching community service programs should benefit elementary schools. This program was to help create a fun classroom and make the learning process more effective by using songs as the vocabulary teaching method. Muhammadiyah Senggotan Elementary School was involved since it claimed English as its concerned subject to attract prospective students. Therefore, there was a great challenge to provide a variety of teaching methods while doing online and face-to-face learning. This program was conducted by teaching third-grade students during the pandemic using face-to-face meetings. Four stages were applied in this program: need analysis, planning, monitoring, and evaluation. The pre-test and post-test results showed a significant difference in students' vocabulary level mastery before and after applying songs in the English teaching and learning process. Hence, this program's sustainability is maintained by increasing the variety of teaching methods through different activities.